2009
DOI: 10.1111/j.1745-7599.2009.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Risks and benefits of parent/child bed sharing

Abstract: If NPs know the benefits and risks regarding co-sleeping and bed sharing, they can better promote safe and culturally congruent family centered care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…A variety of correlates of bed sharing and cosleeping have been found during early infancy. Both bed sharing and cosleeping have been found to facilitate breastfeeding, which is known for its health benefits for the infant (e.g., Ball, 2007;Cunningham, Vally, & Bugeja, 2018;McKenna & McDade, 2005;Sobralske & Gruber, 2009). The uninterrupted mother-infant proximity as a result of cosleeping is thought to be important for establishing breastfeeding, a phenomenon recently referred to as breastsleeping (McKenna & Gettler, 2016).…”
mentioning
confidence: 99%
“…A variety of correlates of bed sharing and cosleeping have been found during early infancy. Both bed sharing and cosleeping have been found to facilitate breastfeeding, which is known for its health benefits for the infant (e.g., Ball, 2007;Cunningham, Vally, & Bugeja, 2018;McKenna & McDade, 2005;Sobralske & Gruber, 2009). The uninterrupted mother-infant proximity as a result of cosleeping is thought to be important for establishing breastfeeding, a phenomenon recently referred to as breastsleeping (McKenna & Gettler, 2016).…”
mentioning
confidence: 99%
“…Sleep practices and habits also are strongly influenced by culture (Sobralske & Gruber, ). For example, in certain cultures such as Sweden, Japan, and Hong Kong, it is normal to co‐sleep, which influences parental decisions about sharing the bed or bedroom with their children (Sobralske & Gruber, ).…”
mentioning
confidence: 99%
“…Sleep practices and habits also are strongly influenced by culture (Sobralske & Gruber, ). For example, in certain cultures such as Sweden, Japan, and Hong Kong, it is normal to co‐sleep, which influences parental decisions about sharing the bed or bedroom with their children (Sobralske & Gruber, ). Research conducted on sleep practices in the United States has found vast differences based on ethnic, racial, regional, and socioeconomic backgrounds (Sobralske & Gruber, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Co-sleeping between parents and their children is hotly debated, and the literature is often polarized because of challenges in establishing associations between bed sharing and many of the suggested risks or benefits, including the association between bed sharing and Sudden Infant Death Syndrome (SIDS) [10]. In addition to the risk of SIDS, there is evidence to suggest that bed sharing may be associated with adverse outcomes such as short sleep duration and markers of sleep quality such as night-time awakenings and bedtime resistance [10], while the suggested benefits of bed sharing include better mother-child bonding, maternal emotional benefits, and better neuro-affective responses to stress in adulthood [11,12,13]. However, a substantial portion of the existing literature on bed sharing has dealt with the risk of SIDS, leaving fewer studies and less evidence related to outcomes of co-sleeping later in childhood.…”
Section: Introductionmentioning
confidence: 99%